Certification against greenwashing in nascent bond markets: lessons from African ESG bonds - Samuel Mutarindwa; Dorothea Schäfer; Andreas Stephan (Eurasian Economic Review, 2024)
Africa is one of the most vulnerable continents to climate change. Climate and sustainability-linked bonds can provide funding to African governments and corporations for projects that help to mitigate climate change, combat biodiversity loss, and foster sustainable development. However, less than 0.3% of the global environmental, social, governance (ESG) bond issuance volume is devoted to projects in Africa. Based on the entire universe of 107 African ESG bonds from 42 governmental and corporate issuers over the period 2010–2023, this paper establishes that ESG bonds provide benefits to both issuers and investors in terms of lower spreads and volatility. Our econometric results highlight that greenwashing is a valid concern for investors in African ESG bonds and certification of ESG bonds makes a difference vis-à-vis the self-labeling of green bonds. Non-certified ESG bonds do not offer similar benefits compared to certified ones. Green macro-financial policy and suitable regulation to prevent greenwashing can foster African ESG-bond markets.
Keywords: G12; G28; K32; Q56; 330; Africa; Sustainable development; ESG bonds; Greenium